Visual cues to female physical attractiveness. - Tovée, M J (1999)
Evolutionary psychology suggests that a woman's sexual attractiveness is based on cues of health and reproductive potential. In recent years, research has focused on the ratio of the width of the waist to the width of the hips (the waist-to-hip ratio (WHR). A low WHR (i.e. a curvaceous body) is believed to correspond to the optimal fat distribution for high fertility, and so this shape should be highly attractive. In this paper we present evidence that weight scaled for height (the body mass index (BMI)) is the primary determinant of sexual attractiveness rather than WHR. BMI is also strongly linked to health and reproductive potential. Furthermore, we show how covariation of apparent BMI and WHR in previous studies led to the overestimation of the importance of WHR in the perception of female attractiveness. Finally, we show how visual cues, such as the perimeter-area ratio (PAR), can provide an accurate and reliable index of an individual's BMI and could be used by an observer to differentiate between potential partners.